Estudo da demanda de energia elétrica do consumidor residencial por uso final - Santos, Ralf Majevski (2016)
Electricity is one of the main elements the advent of modern society, and proof is the consumption of this energy can be used as a leading indicator of economic development and quality of life of any society. Research of demand of electric power through the end-uses of method by type of consumer equipment is gaining ground in the academic area. This study is proposed by means of the end-use method to identify the ownership characteristics and usage habits of electronic equipment residences and the multiple linear regression method guided by the mathematical tool of Ordinary Least Squares - OLS point which equipment that influence consumption of global electricity in the residential consumer's view of Colinas Laranjeiras district situated the city of Serra in the state of Espirito. To do this activity was an elaborate data survey questionnaire in order to get information about consumption characteristics, possession and habits of residential consumers. We arrived at using the Stata. Results obtained of this study indicate in the residential consumer perspective, that the electric shower is still the equipment that has the highest participation in consumption of electricity in the sector, followed by the refrigerator, television and lighting. It is important to highlight that the population studied, 403 interviews were found 0.79 unit incandescent lamp (Halogen), equipment made of resistive filament, per residential unit. The electric shower has a 38% of all consumption of electricity as well as the incandescent lamp, also consists of a resistive filament In this perspective, we can see in the present study the technological improvement lamp equipment, providing increased energy efficiency for its residential sector. However, when analyzing the electrical characteristic of electric shower equipment it is concluded that this technological improvement did not occur at the same intensity in comparison with the lamp.